Proposed domains for assessing postpartum recovery: a concept elicitation study. (14th October 2021) - Sultan, P; Jensen, SE; Taylor, J; El‐Sayed, Y; Carmichael, S; Cella, D; Angst, MS; Gaudilliere, B; Lyell, DJ; Carvalho, B
Abstract : Objective: To propose postpartum recovery domains. Design: Concept elicitation study. Setting: Semi‐structured interviews. Population: Ten writing committee members and 50 stakeholder interviews (23 postpartum women, nine general obstetricians, five maternal and fetal medicine specialists, eight nurses and five obstetric anaesthetists). Methods: Alternating interviews and focus group meetings until concept saturation was achieved (no new themes discussed in three consecutive interviews). Interviews were digitally recorded and transcribed, and an iterative coding process was used to identify domains. Main outcome measures: The primary outcome was to identify recovery domains. We also report key symptoms and concerns. Discussion frequency and importance scores (0–100; 0 = not important; 100 = vitally important to recovery) were used to rank domains. Discussion frequency was used to rank factors helping and hindering recovery, and to determine the greatest challenges experienced postpartum. Results: Thirty‐four interviews and two focus group meetings were performed. The 13 postpartum recovery domains identified, (ranked highest to lowest) were: psychosocial distress, surgical/medical factors, infant feeding and breast health, psychosocial support, pain, physical function, sleep, motherhood experience, infant health, fatigue, appearance, sexual function and cognition. The most frequently discussed factors facilitating postpartum recovery were: family support, lactation/breastfeeding support and partner support. The most frequently discussed factor hindering recovery was inadequate social support. The most frequent challenges reported were: breastfeeding (week 1), breastfeeding (week 3) and sleep (week 6). Conclusions: We propose 13 domains that comprehensively describe recovery in women delivering in a single centre within the USA. This provides a novel framework to study the postpartum recovery process. Tweetable abstract: We propose 13 postpartum recovery domains that provide a framework to study the recovery process following childbirth. Tweetable abstract: We propose 13 postpartum recovery domains that provide a framework to study the recovery process following childbirth.